ANALISIS PENGARUH DANA PERIMBANGAN TERHADAP TINGKAT KEMISKINAN (STUDI KASUS: KABUPATEN/KOTA DI SULAWESI TENGAH TAHUN 2015-2019) - Agum Gumelar; Najwa Khairina (FEB Universitas Sultan Ageng Tirtayasa, 2021)
Poverty is a big problem related to several aspects including: politics, culture, environmental and period economics. This study aims to analyze the effect of the General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund on the Poverty Level with case studies of districts/cities in Central Sulawesi province in 2015 – 2019 which were processed using Panel Data Regression methods and Generalized Least Square (GLS) estimations. The approach used is a quantitative approach because it uses measurements and calculations in research. The processed data is secondary data originating from the Central Statistics Agency. The research findings show that the General Allocation Fund, the Special Allocation Fund and the Revenue Sharing Fund partially and simultaneously have a negative and significant effect on the Poverty Level. This study has a coefficient of determination (R-Square) of 0.98.